Shining a Light on the Connections between Galactic Outflows Seen in Absorption and Emission Lines - Xinfeng Xu; Alaina Henry; Timothy Heckman; Cody Carr; Allison L. Strom; Tucker Jones; Danielle A. Berg; John Chisholm; Dawn Erb; Bethan L. James; Anne Jaskot; Crystal L. Martin; et al. (The Astrophysical Journal)
Galactic outflows provide important feedback effects to regulate the evolution of host galaxies. Two primary diagnostics of outflows are broad and/or blueshifted emission and absorption lines. Even though well-established methods exist to analyze these outflow signatures, connections between them are rarely studied and largely unknown. In this paper, we conduct such a study in a sample of 33 low-redshift starburst galaxies. Their UV absorption lines are detected by the Hubble Space Telescope, and optical emission lines are observed by Keck or the Very Large Telescope. We find that the outflow properties derived from emission and absorption lines are tightly correlated. These include outflow maximum velocity, line width, and radial extent. On average, in the same galaxy, the maximum velocity and line width of outflows measured from emission lines reach only 60%–70% of those from the absorption lines. We also find outflow rates derived from emission lines are consistently lower than those from absorption lines by 0.2–0.5 dex. These findings can be explained by a radial decline in density and a corresponding increase in outflow velocity, combined with the fact that emission line luminosity scales with the square of the density while absorption line depth scales linearly. We test both spherical and biconical outflow models and find that the same radial outflow velocity and density distributions can explain the observed correlations. These results provide novel calibration between galactic outflow properties measured from the two diagnostics and underscore the need for high-fidelity UV and optical spectra to accurately assess galactic feedback effects in high- z galaxies.